Endobronchial valves to occlude bronchopleural fistula and recurrent pneumothorax - Saenghirunvattna, Sawang; Saenghirunvattna, Rungsima; Lalande, Gerard (The Bangkok Medical Journal, 2012)
OBJECTIVES. We present our experiences using endobronchial valves to effectively manage patients presenting with pneumothorax and bronchopleural fistula. MATERIALS AND METHODS. Ten patients underwent the procedure. Seven patients had developed pneumothorax with bronchopleural fistula; two patients were intubated with complicated bronchopleural fistula. One patient had recurrent catamenial right pneumothorax. RESULTS. The procedure was effective in 9 cases (90 percent). The mortality was low, effectiveness was high and achieved in less than 30 minutes. CONCLUSION. This technique is an effective intervention for prolonged air leakage.